Réponses

2013-11-05T20:35:09+01:00
Bonsoir

f) (x + 3) (2x - 1) - 3x (2x +5)
F = (2x²  -x +6x -3) - (6x² +15x)
F = 2x² - x +6 -3 -6x² -15x
F = -4x² -15x +3

  g) (4t +1) (4t -1) - (3t + 2)^{2} 
G = (16t² -4t +4t -1) - (9t² +12t +4)
G = 16t² -1 -9t² +12t +4
G = 7t² +12t +3

 h) 2(s +5) (s - 5) + (4s +3)^{2}  
H = (2s +10) (s -5) + (16s² +24s +9)
H = 2s² -10s +10s -50 + 16s² +24s +9
H = 18s² +24s -41

 i) (3x +4)^{2} - (1 -2x) (6 + x )

I = 9x² +24x +16 - (6 +x -12x -2x²)
I = 9x² -24x +16 -6 -x +12x +2x²
I = 11x² -13x +10